Postnatal biometrical and micrometrical changes of the cauda epididymis in Assam goat from birth to 10 months of age* - SARMA, KAMAL; KALITA, S N; DEV, J (The Indian Journal of Animal Sciences, 2013)
The present work is aimed to elucidate the age-wise post natal development of the corpus epididymis of Assam goats from 0 day to 10 months of age. Assam goats (18) divided into 6 age groups, viz. group 1 (0–day), group 2 (2 months), group 3 (4 months), group 4 (6 months), group 5 (8 months) and group 6 (10 months) consisting of 3 animals in each group were used in this study. After dissection of these organs from the animal’s body, their gross features and biometrical parameters were recorded. The tissues fixed from various organs were utilized for micrometrical studies. The values of majority of the biometrical parameters of corpus, viz. length, width, thickness and weight showed a highly significant variation between different age groups. Bilateral variations of recorded parameters were also noticed between right and left counterparts of this organ. The diameter of the epididymal tubules, height of tubular epithelium and height of the stereo cilia of the cauda epididymides showed a significant increase with advancing age of the male Assam goats.